The distribution of cerebral microbleeds determines their association with arterial stiffness in non‐cardioembolic acute stroke patients. (16th December 2013) - Song, T.‐J.; Kim, J.; Kim, Y. D.; Nam, H. S.; Lee, H. S.; Nam, C. M.; Heo, J. H.
<x xml:space="preserve">Abstract</x> Background and purpose Increased arterial stiffness causes vessel damage in the end‐organs. Therefore small vessels in the brain may be susceptible to increased arterial stiffness. Cerebral microbleeds (CMBs) are topographically or pathophysiologically categorized as deep or infratentorial type and strictly lobar type. Whether the presence and location of CMBs are associated with brachial‐ankle pulse wave velocity (baPWV) which represents a measure of arterial stiffness was investigated. Methods Between June 2006 and January 2012, 1137 consecutive patients diagnosed with non‐cardioembolic acute ischaemic stroke and who underwent baPWV measurement and brain gradient‐echo imaging were enrolled. CMBs were classified as deep or infratentorial or strictly lobar according to their location. Severity of leukoaraiosis was determined using the Fazekas scoring system. Results CMBs were found in 30.7% of the included patients. These patients were older than those without CMBs. Mean baPWV was higher in patients with CMBs than in those without (20 ± 5 m/s vs. 19 ± 5 m/s; P = 0.001). When comparing baPWV according to the location of the CMB, it was higher in the deep or infratentorial CMB group than in the strictly lobar CMB group (22 ± 5 m/s vs. 20 ± 5 m/s; P = 0.001). In univariate and multivariate multinomial logistic regression analyses, baPWV was found to be independently associated with deep or infratentorial CMBs. Conclusions Arterial stiffness was independently associated with deep or infratentorial CMBs but not lobar CMBs. These findings suggest a pathophysiological association between arterial stiffness and CMBs in the deep or infratentorial region.